GAMBARAN PELAKSANAAN PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT PASCA DEKLARASI DESA NELELAMAWANGI WILAYAH KERJA PUSKESMAS ILE BOLENG - Maria Fiona Pius; Marylin Junias; Ribka Limbu (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Community-Based Total Sanitation is the leading example of community-based sanitation in Indonesia. It upholds the non-subsidy principle by enlisting the help of the community to create sanitary and hygienic infrastructure. The problem is the lack of clean water supply facilities and the level of public awareness so that STBM pillars II, IV and V have not yet been implemented. The present analysis is useful research is to get receiving a picture implementation of the Post-Declaration Community-Based Total Sanitation Program in Nelelamawangi Village. This paper was written as a quantitative desk study using survey methods. The sampling technique used in this study uses the propotional sampling method to determine the sample size.Using a proportional sampling method. The population in this study was the people of Nelelamawangi Village, aged 17-60 years, totaling 384 and 196 people were sampled in this study. Study findings demonstrate that it is accurate. that post-declaration STBM Pillar I had been implemented, Post-declaration STBM Pillar II had not been implemented, Post-declaration STBM Pillar III had been implemented, Post-declaration STBM Pillar IV had not been implemented and Post-declaration STBM Pillar V had not been implemented. The conclusion is that pillars in the STBM program have been implemented in pillars I and III and have not been implemented in pillars II, IV and V.